Modulation of in vitro proliferation and cytokine secretion of human lymphocytes by Mentha longifolia extracts - Yahya Asemani; Maryam Bayat; Saeed Malek-Hosseini; Zahra Amirghofran (Mashhad University of Medical Sciences, 2019)
Objective: Mentha longifolia L. Hudson has been used in folk medicine for various purposes especially for its anti-inflammatory effects. Lymphocytes play a central role in development of inflammation. In the present study, we investigated the immunomodulatory effects of different extracts of M. longifolia on human peripheral blood lymphocytes (PBLs), as main players in development of inflammation. Materials and Methods: PBLs stimulated with phytohemagglutinin (PHA) were cultured in the presence of the plant extracts. The effects of the extracts on activation of cells were determined by BrdU assay. The viability of cells was examined by flow cytometry using propidium iodide staining. Also, IFN-γ (T helper 1, TH1) and IL-4 (TH2) secretion was measured by ELISA.  Results: Except for the water extract which had a weak inhibitory effect, treatment of cells with more than 1μg/ml of butanol, hexane, ethyl acetate and dichloromethane extracts resulted in strong inhibition of cells proliferation (IC50 4.6-9.9 µg/ml). Flow cytometry analysis showed that these extracts at ≤10μg/ml were non-cytotoxic. Dichloromethane and ethyl acetate extracts at 10 μg/ml decreased IFN-γ production in a dose-dependent manner from 919±91.1 pg/ml in PHA-only-treated cells to 568±22.6 pg/ml (in dichloromethane-treated cells) and 329±12.3 pg/ml (in ethyl acetate-treated cells) (p